2012
DOI: 10.1016/j.ihj.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Perventricular device closure of isolated muscular ventricular septal defect in infants: A single centre experience

Abstract: Perventricular device closure of isolated mVSD appears feasible option at mid-term follow-up and may either substitute or complement the conventional surgical technique in selected cases depending on institutional paediatric cardiac surgery performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Among all the selected articles, 146 trials were conducted primarily in China 46,12,25–34,36–53,5559,61,63,65160,162,167,168,171–175,180,185,186 , 3 articles were conducted in other Asian countries (one each in India, South Korea and Turkey) 166,169,184 , 10 studies were conducted in the United States 11,62,64,163,170,176,178,179,181,182 , 5 studies were performed in European countries (one each in Austria, France, Germany, Poland, Russian Federation) 35,54,161,165,183 , 2 articles were conducted in South American countries (1 Brazil and 1 Chile) 164,177 , and 1 case-control study was performed in Australia 60 . A total of 108 articles were written in Chinese 5,12,26–29,31,32,36–43,46,70–132,134–159,174,175 , whereas 58 articles were written in English 4,6,11,25,30,3335,44,45,47–69,133,160163,165173,176186 , and the remaining article was written in Portuguese 164 .…”
Section: Resultsmentioning
confidence: 99%
“…Among all the selected articles, 146 trials were conducted primarily in China 46,12,25–34,36–53,5559,61,63,65160,162,167,168,171–175,180,185,186 , 3 articles were conducted in other Asian countries (one each in India, South Korea and Turkey) 166,169,184 , 10 studies were conducted in the United States 11,62,64,163,170,176,178,179,181,182 , 5 studies were performed in European countries (one each in Austria, France, Germany, Poland, Russian Federation) 35,54,161,165,183 , 2 articles were conducted in South American countries (1 Brazil and 1 Chile) 164,177 , and 1 case-control study was performed in Australia 60 . A total of 108 articles were written in Chinese 5,12,26–29,31,32,36–43,46,70–132,134–159,174,175 , whereas 58 articles were written in English 4,6,11,25,30,3335,44,45,47–69,133,160163,165173,176186 , and the remaining article was written in Portuguese 164 .…”
Section: Resultsmentioning
confidence: 99%
“…It is performed by both surgeon and cardiologist in hybrid suit or operating room combining catheterization and surgical techniques [5,6]. Thakkar et al concluded in their series of 24 infants who underwent perventricular device closure of mVSD that in selected high-risk infants, perventricular device closure of isolated mVSD is effective and may either substitute or complement the conventional surgical closure depending on the performance of institutional pediatric cardiac surgery program.…”
Section: Discussionmentioning
confidence: 99%
“…The procedural safety can certainly be improved with more precautions for preventable complications. Until specifically designed hardware is available, very large defect or defects extending into inlet, posterior or apical septum are not suitable for perventricular closure [5]. The major advantages of hybrid approach are: from surgeon's view; i) easy accessibility of m-VSD even in difficult locations ii) no palliative pulmonary artery banding or ventriculotomy required to close the apical m-VSD iii) no ill effects of CPB (cardiopulmonary bypass); from cardiologist's view; i) no limitation for vascular access and sheath size ii) no hemodynamic instability due to arterio-venous looping iii) septum can be approached from anterior (perpendicular angle) but, not from a lateral (tricuspid valve) plane [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study elaborates the technique, complications and outcome of the procedure. 3 The basic question is 'why a perventricular device closure should be performed'? When surgery or intervention alone are not giving any satisfactory result for a given problem or when the combination of two fields become less traumatic to the patient with a better final outcome.…”
mentioning
confidence: 99%